2019
DOI: 10.3329/jme.v48i1.41083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe, Ni and Cr on the corrosion behaviour of hypereutectic Al-Si automotive alloy in 3.5% NaCl solution at different temperature and velocity

Abstract: The main focus of this study is to examine and evaluate the effect of Fe, Ni and Cr on the corrosion behaviour of hypereutectic Al-Si automotive alloy in 3.5% NaCl solution. Experimental information are attained using conventional gravimetric measurements under different solution temperature and velocity and complemented by resistivity, optical micrograph, scanning electron microscopy (SEM) and X-ray analyzer (EDX) investigations. All the alloys show the negative corrosion rate due to formation of a very thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…As also observed by Kaiser et al [9], the white products were identified as being "mushroom-type" layers. The active dissolution of the alloy resulted in Al(OH)3, which is insoluble in water, and precipitates as a white gel with gelatinous flake aspect [35].…”
Section: Immersion Corrosion Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…As also observed by Kaiser et al [9], the white products were identified as being "mushroom-type" layers. The active dissolution of the alloy resulted in Al(OH)3, which is insoluble in water, and precipitates as a white gel with gelatinous flake aspect [35].…”
Section: Immersion Corrosion Resultssupporting
confidence: 64%
“…In other words, the corrosive rate was indeed significantly lower for the alloy with Ni, as assessed after 30-day exposure. In their immersion tests, Kaiser et al [9] observed an inversion of the behavior of the Al alloy containing Ni. While the alloy containing Ni had a greater corrosion rate for shorter periods (1 to 3 days), it demonstrated a lower corrosion rate for longer elapsed times.…”
Section: Immersion Corrosion Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason behind this increase in wear rate is due to the corrosive attack, next formation of passive films on the surface of the sample which acts as a barrier against further corrosion hence the wear rate is low. After some time, the wear rate increases due to the gradual breakdown of the progressively thicker passive films [34].…”
Section: Wear Behaviormentioning
confidence: 99%